Recent updates on metabolite composition and medicinal benefits of mangosteen plant - Wan Mohd Aizat; Ili Nadhirah Jamil; Faridda Hannim Ahmad-Hashim; Normah Mohd Noor (PeerJ, 2019)
Background Mangosteen (Garcinia mangostana L.) fruit has a unique sweet-sour taste and rich in beneficial compounds such as xanthones. Mangosteen has been originally used in various folk medicines to treat diarrhea, wound, and fever. More recently, it has been used as a major component in health supplement products for weight loss and promoting general health. This is perhaps due to its known medicinal benefits including as anti-oxidant and anti-inflammation. Interestingly, the publications related to mangosteen has surged in recent years suggesting its popularity and usefulness in research laboratories. However, there is still no updated reviews (up to 2018) in this booming research area, particularly on its metabolite composition and medicinal benefits. Method In this review, we have covered recent articles within the year of 2016 to 2018, which focuses on several aspects including the latest findings on compound composition from mangosteen fruit as well as its medicinal usages. Result Mangosteen has been vastly used in medicinal areas including as anti-cancer, anti-microbial, and anti-diabetes treatments. Furthermore, we have also described the benefits of mangosteen extract in protecting various human organs such as liver, skin, joint, eye, neuron, bowel, and cardiovascular tissues against disorders and diseases. Conclusion All in all, this review describes the numerous manipulations of mangosteen extracted compounds in medicinal areas and highlights the current trend of its research. This will be important for future directed research and may allow researchers to tackle the next big challenge in mangosteen study; drug development and human applications.